NILAI-NILAI KEARIFAN LOKAL DALAM KEPERCAYAAN LARANGAN TIDUR DI KASUR DI DUSUN KASURAN, MARGODADI, SEYEGAN, SLEMAN - Sabela, Mutiara (KARMAWIBANGGA Historical Studies Journal, 2021)
This study aims to determine the values of local wisdom contained in the belief in the prohibition of sleeping on mattresses in Dusun Kasuran Hamlet, Margodadi, Seyegan Sleman. The method used in this research is qualitative. Using two types of data and data sources, namely primary data and secondary data. Data collection techniques by means of direct observation, in-depth interviews, and documentation. Data analysis techniques with data collection, data reduction, data presentation and drawing conclusions. The technique of checking the validity of the data uses the source triangulation technique and the method triangulation technique. The results of this study indicate that the values of local wisdom in the belief in the prohibition of sleeping on a mattress are historical values, because they have been passed down from generation to generation. Prioritizing religious values, due to fear and public trust. Social values, the emergence of high solidarity between immigrants and community members, Economic values, there are differences in the beds for upper and lower social classes. The stronger the cultural values, the stronger the harmony and peace between the people.